Standardization: a necessity for the documentation and archiving in cultural heritage - Ioannides, Marinos; Hadzilacos, G. (My University, 2003)
The authors will give an overview of the State of the Art in the field of Standardization in the area of Cultural Heritage worldwide. This is especially important due to the fact that Cultural Heritage is currently being influenced by computer technology and utilizing the advantages of digital documentation along with the reconstruction of the past taking on a 3D form. Focusing on the advantages and disadvantages of the modern Information Technology (IT) tools, it will be demonstrated how user dependent data can cause many critical situations. The revolution of IT and the continuous expansion of this technology has set the experts of Cultural Heritage under massive pressure to become familiar with and use the computer technology available. Cultural Heritage data and information has to be reliably read, sorted, indexed, manipulated, retrieved, and communicated between systems nationally and internationally. The use of IT is highly encouraged and has proven itself a vital tool. However, at its present state,“island solutions” have emerged limiting the study area of the researcher which leads to the incompatibility of cataloguing, archiving, presenting and conserving archaeological artefacts, monuments and sites in a unified worldwide format. A” standard”, in Information Technology can be defined as a set of regulations for the guarantee of the protection of the long-term value of digital data for the storage, exchange, sharing, searching and retrieval of information between different users/professionals around the world using the global computer network (Internet) and different Hardware and Software structures. Based on specific examples, the advantages of standardization and dangers of non-standardization of the globalization of e-documentation and e-archiving in Cultural Heritage in the areas of e-libraries and e-museums will be demonstrated and discussed.
Keywords: Databases; Standards; Specification; Data Structure; Documentation; Archiving